Influence of a stepped feed rate on burr formation when drilling Al-5005 - Bahce, Erkan; Ozel, Cihan (Walter de Gruyter Gmbh, 2018)
In this study, the technique of drilling at stepped feed rate is suggested as a new method for reducing the burr size at the exit of a hole in Al-5005, without prolonging the drilling time. The hole was divided into two regions, which were drilled at different feed rates. As a reference for comparison analysis, Al-5005 was drilled at constant drilling parameters. The smallest burr size with constant drilling parameters was obtained at 140 degrees point angle, 0.1 mm x rev(-1) feed rate, and 400 rpm spindle speed. The parameters that mainly effect the burr size were determined to be point angle, feed rate and the spindle speed, respectively. The same material was drilled employing the method of stepped feed rate, where the first region of the hole was drilled at 140 degrees point angle, feed rates of 0.1, 0.2, and 0.3 mm x rev(-1) , and spindle speeds of 400, 800, and 1200 rpm. The second region was drilled with a feed rate that was automatically adjusted by the CNC machine to be one tenth of the feed rate in the first region, without removing the drill bit from the hole. It was observed that, using the stepped feed rate method, the burr height and burr thickness were diminished by 35 % and 25 %, respectively, compared to constant drilling parameters.
Keywords: Drilling; stepped feed rate; Al-5005; burr Size; CNC